2014
DOI: 10.5539/jas.v6n9p1
|View full text |Cite
|
Sign up to set email alerts
|

Cultivars, Planting Dates, and Row Spacing Effects on Sesame Seed Yield and Mineral Composition

Abstract: This study was conducted to determine if sesame (Sesamum indicum L., Pedaliaceae) could be grown in Virginia. Five proprietary sesame cultivars (22K, S26, S28, S30, and S32) were planted on May 23 and June 8 during 2011 and on July 9 and July 17 during 2012 using two row spacings (37.5 or 75 cm). Effects of cultivars and row spacings on seed yield, and contents of protein and minerals were, generally, non-significant. Effects of planting dates were significant for most traits under study except for contents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…In the current study, all cultivars reached peak vegetative N accumulation at the same time (mid-bloom), which supports earlier research that found peak leaf tissue N accumulation occurred approximately DAP for 10 sesame genotypes (Pawar et al, 2003). The similar quantity of N partitioned to seed among medium-maturing cultivars in the current study also complements earlier research in Virginia that showed similar amounts of secondary and micronutrients allocated to seed among medium-maturing cultivars, including S30 and S32 (Bhardwaj et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, all cultivars reached peak vegetative N accumulation at the same time (mid-bloom), which supports earlier research that found peak leaf tissue N accumulation occurred approximately DAP for 10 sesame genotypes (Pawar et al, 2003). The similar quantity of N partitioned to seed among medium-maturing cultivars in the current study also complements earlier research in Virginia that showed similar amounts of secondary and micronutrients allocated to seed among medium-maturing cultivars, including S30 and S32 (Bhardwaj et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Different response between thirteen sesame genotypes in two locations were shown due to the different environmental variations and soil conditions for the two locations, indicating that sesame seed yield was affected by environmental conditions prevailed in the two locations, also providing evidence for the necessity of testing studied genotypes in multiple environments and Stability measurement, therefore the stability parameters for each genotype. Similar finding results was obtained by Bhardwaj et al (2014), Eryigit et al (2016) and Kashani et al (2015). While Anastasi et al (2017) determined sesame seed yields between 1900 to 3500 kg ha -1 .…”
Section: Mean Performance For Seed Yieldsupporting
confidence: 89%
“…Accordingly, the enhancements in sesame yields, yield components and oil percentage with early planting date may be due to that the plants had optimum vegetative growth, adequate photosynthetic activity and more assimilates than planting latter. Bhardwaj et al (2014) indicated that earlier sowing date resulted in significantly higher seed yield by about 56%. Abdalla et al (2004) found that flowering and maturity periods were reduced by 18 days due to delayed sowing.…”
Section: Effect Of Sowing Datesmentioning
confidence: 99%